Listening to the voices: The experiences of African American female student athletes - Bruening, J. E.; Armstrong, K. L.; Pastore, D. L. (Research Quarterly for Exercise and Sport, 2004)
"Women of color . . .have historically been silenced in society and sport" (Smith, 1992, p. 228). This study examined the sport participation patterns of 12 African American female collegiate student athletes using qualitative methods. Data were collected at a large midwestern university during the 1998-99 academic year. An emergent theme was the effect of silencing by the media, athletic administrators, coaches, and other student athletes on the experiences of African American female student athletes. The findings are presented in the following order: the theoretical framework for the study, an introduction to silencing, an overview of the research analyses, a description of the research setting, and a presentation of the data surrounding the theme of silencing as told through the participants` voices. Following these sections is a discussion and suggestions for future research.